2021
DOI: 10.1093/esr/jcab003
|View full text |Cite
|
Sign up to set email alerts
|

From Social Assistance to Self-Sufficiency: Low Income Work as a Stepping Stone

Abstract: Welfare reforms often focus on stimulating employment among benefit recipients, based on the theoretical mechanism that the performance of low income work will serve as a stepping stone towards financial self-sufficiency. Alternative theories, however, argue that the acceptance of low income work will reduce job search intensity and can signal low productivity, and therefore will not enable people to support themselves. Using longitudinal administrative data and discrete time linear probability models, we foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…Additionally, the dead-end of supplementary part-time jobs for women may also (partly) be driven by supply-side effects arising if women change preferences after entering part-time employment and become less interested in working full-time (Johnson & Pencavel 1984, Hotz et al 1988). The differential effect of part-time supplementary jobs for men and women is consistent with international evidence from Kyyrä et al (2013) for Denmark and from Boschman et al (2021) for the Netherlands, who found that part-time work during benefit receipt is less beneficial for women.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Additionally, the dead-end of supplementary part-time jobs for women may also (partly) be driven by supply-side effects arising if women change preferences after entering part-time employment and become less interested in working full-time (Johnson & Pencavel 1984, Hotz et al 1988). The differential effect of part-time supplementary jobs for men and women is consistent with international evidence from Kyyrä et al (2013) for Denmark and from Boschman et al (2021) for the Netherlands, who found that part-time work during benefit receipt is less beneficial for women.…”
Section: Resultssupporting
confidence: 84%
“…Second, our paper relates to the stepping stone effects literature, which analyzes whether the take-up of certain employment types enhances the chances of subsequent regular employment. More precisely, the existence of stepping stone effects has been investigated (and in most cases also confirmed) for low-wage employment 4 (Uhlendorff 2006, Knabe & Plum 2013, Mosthaf 2014, Cai et al 2018, Boschman et al 2021, for temporary agency work (Kvasnicka 2009, de Graaf-Zijl et al 2011, Gebel 2013, Jahn & Rosholm 2014, for atypical work in general (Auray & Lepage-Saucier 2021), for (subsidized) part-time jobs (Cockx et al 2013, Kyyrä et al 2013, Nightingale 2020) and for marginal employment 5 (Freier & Steiner 2008, Caliendo et al 2016, Lietzmann et al 2017.…”
Section: Introductionmentioning
confidence: 97%
“…Whether one has a full-time job or only a marginal Minijob does not seem to matter. This finding contributes to the ongoing debate about whether marginal employment acts as a stepping stone into the labor market or a poverty trap (Booth et al, 2002;Lietzmann et al, 2017;Boschman et al, 2021). While Minijobs provide latent functions similar to those of other forms of employment, they fail to mitigate financial strain.…”
Section: Limitations and Implicationsmentioning
confidence: 76%
“…Second, our paper relates to the stepping stone effects literature, which analyzes whether the take-up of certain employment types enhances the chances of subsequent regular employment. More precisely, the existence of stepping stone effects has been investigated (and in most cases also confirmed) for low-wage employment 6 (Boschman et al, 2021;Cai et al, 2018;Knabe & Plum, 2013;Mosthaf, 2014;Mosthaf et al, 2014;Uhlendorff, 2006), for temporary agency work (de Graaf-Zijl et al, 2011;Gebel, 2013;Jahn & Rosholm, 2014;Kvasnicka, 2009), for atypical work in general (Auray & Lepage-Saucier, 2021), for (subsidized) part-time jobs (Cockx et al, 2013;Kyyrä, 2010;Kyyrä et al, 2013;Nightingale, 2020) and for marginal employment 7 (Caliendo et al, 2016;Freier & Steiner, 2008;Lietzmann et al, 2017). increased from 400 to 450 euros in 2013) where employees are exempted from taxes and social security contributions and employers pay an overall reduced rate of social security contributions.…”
mentioning
confidence: 98%
“…Moreover, in contrast to the current paper, these studies do not differentiate between welfare recipients with and without a supplementary job. While the studies of Kyyrä (2010) and Boschman et al (2021) also investigate whether supplementary jobs serve as a stepping stone into employment, our study offers additional insights. We further distinguish between welfare exits into part-and full-time employment, which is particularly relevant since the risk of future welfare dependency may differ between part-and full-time jobs (without welfare).…”
mentioning
confidence: 99%